The Philippine local water sector institutional issues in supply governance - Velasco, Lawrence G.; Diokno-Sicat, Charlotte Justin; Castillo, Angel Faye G.; Maddawin, Ricxie B. (2021)
Aligned with the United Nations' Sustainable Development Goal 6 to "ensure availability ang sustainable management of water and sanitation for all", the Philippine Development Plan 2017-2022 recognizes the importance of water supply and sanitation (WSS) in accelerating the country's infrastructure development. The National Economic Development Authority's Philippine Water Supply and Sanitation Master Plan 2019-2030 presents actions for universal access to safe WSS by 2030. Although national and international goals are already in place to attain water security, water service delivery remains devolved and dependent on the local governments. The sector also receives uneven public investments through the national government. With the implementation of the Mandanas ruling affirmed by the Supreme Court, which gives local governments increased grants, strengthened devolved functions, and reduced program assistance from the national government, water service delivery will continue to be the local government's responsibility. For decades, the literature has emphasized the need to address fragmentation among water institutions and in regulations that have resulted in uneven and inefficient investments. This study explains fragmentation by answering the question: " What institutional and regulatory factors affect the magnitude of "investment on the local water sector?" It presents the current potable water access in the country and shows the resultant uneven public investments. It reviews the current mandates of the two main regulating bodies for potable water access in local communities and identifies various overlaps and ambiguities in managing the sector. The results show the need to streamline and align the sectors' unclear economic and technical regulations with its operating standards to avoid fragmentation. In addition, investment coordination must be improved to ensure strategic investments and efficient use of limited financing. There should be a consolidated and complete database of water service providers, as well as key performance indicators and other data, to better monitor the investments in the local water sector
Keywords: Sustainability; Water supply management; Water-supply